The strategy of negative representation of “others” in political discourse: tactics of implementation - Kalishchuk, Diana (Lesya Ukrainka Eastern European National University, 2014)
The article deals with the analysis of the strategy of negative presentation of “others” as local strategy within the global discourse strategy. The strategy of influence is considered to be the global strategy of political discourse. Persuasiveness is considered to be a universal property of political discourse and it manifests itself in form of speech manipulation. Political manipulation is treated as specific type of influence. The author interprets manipulation as peculiar communicative speech strategy, to realize which the speaker chooses certain methods and tactics and selects certain language means. The most common local strategies are the strategies of positive self-presentation and negative presentation of “others”. The paper outlines the tactics to realize the strategy of negative presentation of “others”, namely such tactics as super-generality, exemplification, transposition and attribution, which are considered to be the most common ones. Although no language means are meant to be used for manipulation, the research has proved that almost any language means may be used for that.
Keywords: political discourse; manipulation; local strategy; global strategy; tactic